1998
DOI: 10.1006/jmsc.1998.0375
|View full text |Cite
|
Sign up to set email alerts
|

Long-term phytoplankton studies in the Bahía Blanca estuary, Argentina

Abstract: Phytoplankton composition and abundance in the Bahía Blanca estuary, Argentina, have been studied from 1978 to 1993; also water temperature, salinity, transparency, and nutrient concentrations. The pattern of seasonal distribution showed a winter/ early spring bloom of diatoms, dominated by Thalassiosira spp., as the most important event in the annual cycle. Annual means of temperature and salinity showed relatively minor variations. Nutrient concentrations (nitrate, silicate, and phosphate) exhibited a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 13 publications
1
23
1
3
Order By: Relevance
“…28 days (G. Perillo unpublished). The water column is generally well mixed all year-round (Gayoso 1998). Two freshwater tributaries enter the estuary from the northern shore, the Sauce Chico River and the Napostá Grande Creek, with a mean annual runoff of 1.9 and 0.8 m 3 s -1 , respectively (Melo and Limbozzi 2008).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…28 days (G. Perillo unpublished). The water column is generally well mixed all year-round (Gayoso 1998). Two freshwater tributaries enter the estuary from the northern shore, the Sauce Chico River and the Napostá Grande Creek, with a mean annual runoff of 1.9 and 0.8 m 3 s -1 , respectively (Melo and Limbozzi 2008).…”
Section: Study Areamentioning
confidence: 99%
“…All published phytoplankton data (Gayoso 1989(Gayoso , 1998(Gayoso , 1999Pettigrosso and Popovich 2009;Popovich 1997Popovich , 2004Popovich and Gayoso 1999;Popovich and Marcovecchio 2008;Popovich et al 2008a) were compiled to compare the phytoplankton annual pattern observed in the period 2006-2008 with the one previously described in the estuary.…”
Section: Historical Data Compilationmentioning
confidence: 99%
“…Dissolved oxygen showed a seasonal distribution pattern, with the maximum in winter owing to low temperatures and production from the phytoplankton bloom (Gayoso, 1998), and variations laying between 5.4 and 11.6 mg L -1 . These results allow to support that this environment does not shown oxygen deficiency, because values of "severe hipoxia" (< 4 mg L -1 ) or below "minimum acceptable level" (< 2 mg L -1 ) for coastal and estuarine waters (Windsor, 1985;Rabalais et al, 1991) have never been recorded.…”
Section: Environmental Parametersmentioning
confidence: 99%
“…Diatoms of the Thalassiosira genus are important components of phytoplankton and dominate blooms in eutrophic water (Harris et al 1995;Gayoso 1998). Thalassiosira pseudonana is a small centric diatom of 3-5 mm in diameter and has a wide geographical distribution (Guillard and Ryther 1962;Hasle and Heimdal 1970).…”
Section: Introductionmentioning
confidence: 99%